(untitled) (REMUNOM, 2026)
Workplace harassment is a continuous and intentional process of psychological violence that generates significant impacts on workers’ mental health, interpersonal relationships, and organizational performance, often related to structural and cultural factors within companies. In the context of Higher Education Institutions, such practices take on specific contours due to asymmetrical hierarchical relationships and pressures for academic productivity, often made invisible by institutional management. Given this scenario, the present study aimed to analyze the relationship between the perception of organizational support, the occurrence of workplace harassment, and its affective impacts on employees of public higher education institutions in the state of Rio Grande do Norte. This is a quantitative study with a sample of 120 public employees from HEIs. The results showed that organizational support exerts a significant preventive effect on workplace harassment, presenting a negative relationship with both general harassment and its interpersonal and professional dimensions. However, this support proves limited in mitigating emotional damage after the occurrence of violence, indicating that its effects are predominantly preventive